The Relationship Between Health Locus of Control and Compliance in Rural Communities - Syahputri, Rahayu (Acta Psychologia, 2022)
The purpose of this study is to empirically test the relationship between health locus of control and compliance in rural communities. rural communities who participated in this study. This means the individual's belief that their health is controlled by themselves in relation to the individual's adherence to medical care. The higher the individual's internal control in controlling health, the higher the individual's level of compliance in carrying out medical treatment and vice versa. There is a positive and linear relationship between powerful others HLC and compliance in rural communities who participated in this study. This means an individual's belief that another person (doctor, midwife or family) is in control of their health related to that individual's adherence to medical treatment. The higher their belief that their health is controlled by others, the higher the level of compliance in carrying out medical treatment and vice versa. There is no relationship between HLC chance and compliance in rural communities who participated in this study. Chance, luck, and destiny have nothing to do with individual adherence to medicine. Based on the description of the research data on the internal HLC variables, it was found that the internal HLC average of the research subjects was in the very high category.